Terapia de fotobiomodulação aplicada em associação ao exercício físico em indivíduos saudáveis: avaliação de diferentes momentos de irradiação no treinamento de força de membros inferiores e evidência científica atual - Vanin, Adriane Aver (2017)
The effects of photobiomodulation therapy (PBMT) has been widely studied by some research groups. We know that there are positive results with light application on improvement of muscle performance and reduction of fatigue. However, there are few studies showing its´ effects on strength training. Therefore, the aim of this study was to verify the effects of PBMT, with the combination of different sources of light, applied at different moments (before, after, before and after) regarding to training sessions in healthy people between 18 and 35 years old. For this, two randomized clinical trials were proposed, each proposing a kind of strength training with application of active or placebo PBMT before and / or after exercise. A total of 96 volunteers were recruited, 48 participated in strength training 1, proposed twice weekly, and the second group of 48 participated in training 2, proposed for three times a week. Both exercises lasted 12 weeks and the peak torque was evaluated through the maximal voluntary contraction test (MVC) in isokinetic dynamometer, strength by 1-RM test in the leg press and leg extension exercises and thigh circumference of the lower limbs bilaterally. Assessments are carried out before any procedure (baseline) and after 4, 8 and 12 weeks after beginning of strength training. On training 1, participants obtained better results results in the MVC test and also in the 1-RM tests for both exercises (leg press and leg extension) when irradiated with PBMT only prior to the training sessions, confirming positively the interference of the PBMT in the gain of muscle strength when applied previously to the exercise session in a protocol of 2 times a week. For training 2, there was an increase in strength with the training, but no statistically significant results were observed for any of the variables proposed in the intergroup comparison. In addition, due to the great dynamism in research in this area, a systematic review was developed in which it was compiled the current knowledge on the effects of PBMT in combination with exercise in improving muscular performance and reducing signs of fatigue in athletes and healthy people. It was possible quantitative analysis (meta-analysis) for some variables related to performance and muscular fatigue. In general, positive results were found using Laser, LED or the combination of both in a wavelength range of 655 to 950 nm. Most positive results were observed with an energy dose range of 20 to 60 Joules for small muscle groups (85% of included studies with positive effects) and 60J to 300J for large muscle groups (75% of included studies with positive effects) and maximum power of 200mW per diode. However, due to the low methodological quality, small sample size, large variability of exercise protocols and parameters of the PBMT, further research is needed to establish a consensus.